ANALISIS LAPORAN KEUANGAN USAHA MIKRO, KECIL, MENENGAH BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH PADA PELAKU USAHA DAGANG WARUNG DI ANGKRINGAN LESTARI - Setiawan, Husein Tri; Jaeng , Wihelmina M. Yulia; Lamawitak, Paulus Libu (Universitas Nusa Nipa Maumere, 2025)
This research aimed to examine the presentation of financial statements at the Angkringan Lestari food stall and to evaluate the preparation of financial statements based on Financial Accounting Standards for Micro, Small, and Medium Entities for MSMEs (Micro, Small, and Medium Enterprises) operating at Angkringan Lestari. This research used a qualitative approach using the Miles and Huberman analysis method, which includes data reduction, data presentation, and conclusion drawing. Data were collected through observation, interviews, and documentation. The results showed that the financial recording system applied by the Angkringan Lestari MSME was very simple, limited to recording expenses, income, and debts. Consequently, the MSME faced challenges in preparing its financial statements, including the owner's limited understanding of Financial Accounting Standards for Micro, Small, and Medium Entities and the absence of dedicated staff responsible for financial statement preparation.